INVESTMENT DOMINANTS OF THE IMPLEMENTATION OF THE INNOVATIVE MODEL OF SUSTAINABLE USE OF FRESHWATER RESOURCES AT THE NATIONAL AND REGIONAL LEVELS - SERBOV, Nikolay; IRTYSHCHEVA, Inna; PAVLENKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Of course, in addition to an effective system of control and administration of water resources, essential factors in the implementation of an innovative model of sustainable use of freshwater resources in the regions are the introduction of new technologies aimed at cleaning freshwater water bodies and promoting the rational use of water resources. The activation of such works requires sufficient funding and the attraction of additional investments in the industry. The article aims to research investment dominants in implementing an innovative model of sustainable use of freshwater resources at the national and regional levels. An analysis of investment support for developing the freshwater resource management system in Ukraine was carried out. The analysis showed that over the past ten years, the number of investments increased by 115%, which positively affected the state of water bodies and contributed to the reduction of water consumption in the economy. However, given the high level of wear and tear of the water management infrastructure, which according to the State Statistics Service, is an average of 63% of the available investments, it is not enough for the transition of water management to an innovative model of sustainable development. In addition, the conducted studies showed that more than 98% of investments are directed primarily to eliminating current problems in water management, reorganizing the industry, and partial modernization of water treatment facilities and centralized water supply systems. Almost no funds are invested in developing innovative activities in this area. The main areas of improvement of the system of investment support for innovative development of water management systems in the region are outlined, including improvement of regulatory and legal support and development of public-private partnership, in particular in the form of ESCO contracts; the use of freshwater resources for aquaculture production, which will increase the economic efficiency of the use of surface water bodies, will contribute to the attraction of investments in the industry and strengthening of food security; creation of conditions for attracting foreign investments, in particular in the construction and modernization of infrastructure; intensification of work in the direction of attracting international finances: grants, participation in international programs for the protection and restoration of water resources, etc.